AB1082 Specific Sonographic Measures of Effusion Associate with Pain but not Response to Intra-Articular Steroid Injection in Knee Osteoarthritis. (9th June 2015) - Klocke, R.; Hirsch, G.; Kitas, G.
Abstract : Background: Valid and readily available imaging biomarkers in knee osteoarthritis (OA) are still lacking. Previous sonographic studies of effusion and synovial thickening in relation to pain and response to intra-articular corticosteroid injection (IACI) have been negative or inconclusive, often using binary criteria for effusion/synovial thickening for analysis, and/or uncertain definitions of scanning technique. Objectives: To investigate the association between measures of sonographic effusion/synovial thickening at specific sites of the supra-patellar pouch (SPP) and knee pain and change of knee pain following IACI in knee OA. Methods: In a prospective secondary-care based, observational study, 105 subjects with knee OA (mean age 63.6 years, 59% female, median symptom duration 36 months) underwent baseline sonographic measurement in triplicates of maximal effusion and synovial layer thickness [mm] at the medial (transverse), mid (longitudinal)and lateral (transverse) SPP (as defined by patellar margins), of the maximally extended, relaxed knee. Knee pain was assessed by WOMAC questionnaire [0-500mm] at baseline and 3 weeks after IACI of 40 mg triamcinolone plus lignocaine injected by a separate clinician, using anatomical landmarks. Results: Mean WOMAC pain at baseline was 265.7 (SD 95.5) and 148.8 (133.5) at 3 weeks. Effusion and synovial thickness was maximal at the lateral SPP (Table 1 ). Univariate linear regression with baseline pain/percentage pain change as dependent variable returned a significant r for medial, lateral and mean SPP effusion with baseline pain, but not percentage pain change. The variance of baseline pain explained by lateral and mean SPP effusion was very similar at 6.6 and 6.7%, respectively. Interrater-ICC coefficient on a sub-sample was 0.92. Synovial thickness showed no significant correlation with pain or pain change. Mean SPP effusion thickness showed a significant correlation with high-sensitivity CRP at baseline (Pearson's r 0.273, p=0.009). Conclusions: This study suggests that targeted sonographic measurement of effusion thickness at the lateral supra-patellar pouch may predict some of the pain in knee OA, but not response to IACI. The correlation of mean effusion thickness and hsCRP also indicates that effusion in knee OA may represent a measure of inflammation. Disclosure of Interest: None declared